The reaction is (a reação é)
(C6H4(OH)2(aq) + H2O2(aq) --> C6H4O2(aq) + H2O(L) ........(i)
The other reaction given are (A outra reação dada é)
C6H4(OH)2(aq) ---> C6H4(OH)2(aq) + H2(g) .......(ii) ΔH = 177 kJ
2H2O2(aq) ----> 2H2O(l) + O2(g) ..................................(iii) ΔH = -189.3
2H2(g) + O2(g) ----> 2H2O (l) .....................................(iv) ΔH =-572 kJ
We can obtain equation (i) from equation (ii), (iii) and (iv) as
[Podemos obter a equação (i) da equação (ii), (iii) e (iv) como]
equation (i) = equation (ii) + 0.5 X equation (iii) + 0.5 X equation (iv)
[equação (i) = equação (ii) + 0.5 X equação (iii) + 0.5 X equação (iv)]
So ΔH1 = ΔH(ii) + 0.5 X ΔH(iii) + 0.5 X ΔH(iv)
= 177 + 0.5 X (-189.3) + 0.5 X(-572) = -203.65 kJ